2021
DOI: 10.1021/acs.energyfuels.1c01948
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Chemical Kinetic Study of Acetaldehyde Oxidation and Its Interaction with NOx

Abstract: This work entails a detailed modeling and experimental study for the oxidation kinetics of acetaldehyde (CH3CHO) and its interaction with NO x . The ignition behavior of CH3CHO/O2/Ar has been investigated in a shock tube over the temperature range of 1149 to 1542 K, with equivalence ratios of 0.5 and 1.0 and pressures near 1.2 bar. Absorbance–time profiles of acetaldehyde were recorded using a mid-IR laser during the autoignition measurements. A comprehensive kinetic model has been developed to quantitatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 101 publications
3
19
0
Order By: Relevance
“…We adopted the 13DO submechanism from the recent work of Wildenberg et al However, such simple adoption did not yield satisfactory results against the experimental data, especially IDTs and speciation data, mainly due to the different base chemistry and new reaction rate of the reaction 13DO (COCOC) = CH 3 CHO + CH 2 O in the kinetic models, which is discussed below. Wildenberg et al adopted AramcoMech 3.0 for the base model, whereas our current model is an extension of our previous work with the base model developed over the past 5 years. , We observed that acetaldehyde (CH 3 CHO) is a major intermediate species during 13DO oxidation and is important for the 13DO (see Section ) oxidation. AramcoMech 3.0 does not include the low-temperature chemistry of CH 3 CHO, particularly internal H-abstraction of CH 3 CO 3 and finally leading to ketohydroperoxide, whereas our kinetic model includes these reactions.…”
Section: Kinetic Modelingmentioning
confidence: 85%
See 3 more Smart Citations
“…We adopted the 13DO submechanism from the recent work of Wildenberg et al However, such simple adoption did not yield satisfactory results against the experimental data, especially IDTs and speciation data, mainly due to the different base chemistry and new reaction rate of the reaction 13DO (COCOC) = CH 3 CHO + CH 2 O in the kinetic models, which is discussed below. Wildenberg et al adopted AramcoMech 3.0 for the base model, whereas our current model is an extension of our previous work with the base model developed over the past 5 years. , We observed that acetaldehyde (CH 3 CHO) is a major intermediate species during 13DO oxidation and is important for the 13DO (see Section ) oxidation. AramcoMech 3.0 does not include the low-temperature chemistry of CH 3 CHO, particularly internal H-abstraction of CH 3 CO 3 and finally leading to ketohydroperoxide, whereas our kinetic model includes these reactions.…”
Section: Kinetic Modelingmentioning
confidence: 85%
“…Wildenberg et al adopted AramcoMech 3.0 for the base model, whereas our current model is an extension of our previous work with the base model developed over the past 5 years. , We observed that acetaldehyde (CH 3 CHO) is a major intermediate species during 13DO oxidation and is important for the 13DO (see Section ) oxidation. AramcoMech 3.0 does not include the low-temperature chemistry of CH 3 CHO, particularly internal H-abstraction of CH 3 CO 3 and finally leading to ketohydroperoxide, whereas our kinetic model includes these reactions. We updated the rate parameters within the 13DO submechanism wherever deemed necessary to capture the experimental data over a wide range of conditions.…”
Section: Kinetic Modelingmentioning
confidence: 85%
See 2 more Smart Citations
“…Li et al 22 reported their experimental and modelling study of the thermal decomposition of cyclopentanone in a flow reactor. Shrestha et al 23 explored the effect of NOx on the oxidation of acetaldehyde in a shock tube, proposing a comprehensive kinetic model to explain the obtained experimental results. The last paper in the group discussed the oxidation of ammonia.…”
Section: ■ Combustion Of Other Biofuelsmentioning
confidence: 99%